Transfusion-related acute lung injury (TRALI): Potential pathways of development, strategies for prevention and treatment, and future research directions. (May 2022) - Tung, John-Paul; Chiaretti, Sara; Dean, Melinda M.; Sultana, Annette J.; Reade, Michael C.; Fung, Yoke Lin
Abstract: Transfusion-related acute lung injury (TRALI) can occur during or after a transfusion, and remains a leading cause of transfusion-associated morbidity and mortality. TRALI is caused by the transfusion of either anti-leukocyte antibodies or biological response modifiers (BRMs). Experimental evidence suggests at least six different pathways that antibody-mediated TRALI might follow: (i) two hit neutrophil activation; (ii) monocyte and neutrophil dependent; (iii) endothelial cell, neutrophil Fc receptor, platelet and neutrophil extracellular trap dependent; (iv) direct monocyte activation; (v) direct endothelial cell activation; and (vi) endothelial cell, complement and monocyte dependent. Two of these pathways (i and v) also apply to BRM-mediated TRALI. Different antibodies or BRMs might initiate different pathways. Even though six pathways are described, these might not be distinct, and might instead be interlinked or proceed concurrently. The different pathways converge upon reactive oxygen species release which damages pulmonary endothelium, precipitating fluid leakage and the clinical symptoms of TRALI. Additional pathways to the six described are likely to also contribute to TRALI pathogenesis, and this requires further investigation. This review also discusses evidence of protective mechanisms and their implications for clinical TRALI treatment. Finally, it suggests directions for future research to support the translation of these findings into strategies to prevent and treat clinical TRALI.